2015
DOI: 10.1159/000375392
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Treatment Effects on Progression-Free Survival and Overall Survival in Multiple Myeloma: A Systematic Review and Meta-Analysis of Published Clinical Trial Data

Abstract: Background: Demonstrating improved overall survival (OS) with new multiple myeloma (MM) treatments is becoming difficult because of extended survival, so progression-free survival (PFS) is commonly used as a surrogate endpoint for OS. We evaluated PFS as a potential surrogate for OS by examining whether observed treatment effects on PFS are positively associated with treatment effects on OS in MM. Methods: A systematic literature review identified 21 randomized control trials reporting hazard ratios (HRs) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 42 publications
1
22
2
Order By: Relevance
“…However, in recent past (since 1990), a trend of decreased use of OS and increased use of event‐free survival/PFS as a primary endpoint has occurred in NHL . Furthermore, the surrogacy of PFS for OS has been established in various cancer settings such as colorectal cancer, gastrointestinal stromal tumors, metastatic prostate cancer, and hematological malignancies, including chronic lymphocytic leukemia, NHL, and MM . For instance, Lee et al found a good correlation ( R 2 = 0.90) between PFS and OS in aggressive NHL, although they could not establish the same correlation between PFS and OS in indolent NHL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in recent past (since 1990), a trend of decreased use of OS and increased use of event‐free survival/PFS as a primary endpoint has occurred in NHL . Furthermore, the surrogacy of PFS for OS has been established in various cancer settings such as colorectal cancer, gastrointestinal stromal tumors, metastatic prostate cancer, and hematological malignancies, including chronic lymphocytic leukemia, NHL, and MM . For instance, Lee et al found a good correlation ( R 2 = 0.90) between PFS and OS in aggressive NHL, although they could not establish the same correlation between PFS and OS in indolent NHL.…”
Section: Discussionmentioning
confidence: 99%
“…22 Furthermore, the surrogacy of PFS for OS has been established in various cancer settings such as colorectal cancer, 23,24 gastrointestinal stromal tumors, 25 metastatic prostate cancer, 3 and hematological malignancies, including chronic lymphocytic leukemia, 26 NHL, 22 and MM. 27,28 For instance, Lee et al 22 Because there may be difficulties in using PFS as an endpoint because of the length of follow-up that is required, particularly in indolent forms of NHL, ORR and CR rates are increasingly used as primary or secondary endpoints in clinical trials. 11,29 However, in hematological malignancies, few studies have determined the relationship between response rates and survival-based endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…2) Treatment line (14,21,22,25,26,28,33,34,36,40,41,49,52) In some cases the analysis cannot validate the surrogacy for first line therapy, as distinct 3) Year of the trial (11,13,15,16,18,19,22,28,(31)(32)(33)(34)40) The importance of the year in which the clinical trial was conducted or published was explained by the number of drugs available having increased (11 and because the criteria applied to measure progression have changed (e.g. RECIST published in 2000 was modified in 2010 to mRECIST (54)).…”
Section: ) Type Of Treatment And/or Therapymentioning
confidence: 99%
“…Overall survival has its limitations however, namely loss to follow‐up due to the long survival rates, cost of these large studies, and confounding of the novel therapy survival benefit due to the ever expanding number of subsequent therapies. Thus, progression‐free survival (PFS) is currently the standard primary endpoint in multiple myeloma . However, even the time to evaluate PFS is becoming prohibitive for development of novel therapies with better treatments becoming available and with combination therapy becoming the standard of care.…”
Section: Introductionmentioning
confidence: 99%